Researching the Supply Chain Management for Human Resources by Virtue of the Techno-economic Paradigm Concept - V. Krasova, Elena (International Journal of Supply Chain Management, 2020)
The supply chain for human resource management is one of the most popular, actual, and versatile areas of economic science. The main scientific and practical problem of the research is the insufficient knowledge of the reasons for the supply chain for human resource management development against the background of an extensive accumulation of theoretical material, the inconsistency of empirical estimates of various processes and phenomena associated with the formation and use of human capital. The purpose of the research is to study the main stages of the supply chain for human resource management evolution from the point of view of the techno-economic paradigm concept. The methodological basis of the research is the theses of the classical economic theory and the supply chain for human resource management in all its diversity, the techno-economic paradigm concept, as well as the innovative development concept. The article considers the historical periodization of the capitalist economy development, explores the evolution of views on the human’s role in the world public production. It is concluded that the human’s role in the world public production is determined, first of all, by the prevailing techno-economic paradigm. A scientific base for researching the human capital and its main components is created and developed in accordance with the techno-economic paradigm and its appropriate structure type. The article covers the time period from the end of the XVIII century until the 90s of XX century.